Faktor Maternal sebagai Determinan Stunting di Kawasan Timur Indonesia: Analisis Data Indonesian Family Life Survey 5 - Iing Merillarosa Kharisma Wardani; Siti Nurrochmah; Dian Mawarni (FORIKES, 2022)
The proportion of children under five with stunting in Indonesia is still high at 27.7% in 2019. Provinces in the Eastern Region of Indonesia have a higher proportion of children under five with stunting compared to provinces in the Western Region of Indonesia. The purpose of this study was to examine the determinants of stunting in children aged 1-5 years in Eastern Indonesia by examining maternal factors. The study used secondary data taken from the Indonesian Family Life Survey 5 (IFLS 5). The sample in this study were all children aged 1-5 years living in Eastern Indonesia who were respondents in IFLS 5. The dependent variable was the incidence of stunting, while the independent variables included maternal height, maternal education level, and maternal age during pregnancy. Data were analyzed using logistic regression test. The results showed that the p-value for maternal height = 0.000), education level = 0.001, and maternal age at pregnancy = 0.039. Thus, it can be concluded that maternal factors consisting of maternal height, maternal education level, and maternal age during pregnancy are determinants of stunting in children under five in Eastern Indonesia.Keywords: stunting; toddler; maternal factors; mother's height; mother's education; mother's age at pregnancy ABSTRAK Proporsi balita dengan stunting di Indonesia masih tinggi yaitu 27,7% pada tahun 2019. Provinsi yang berada di Kawasan Timur Indonesia memiliki proporsi balita dengan stunting yang lebih tinggi dibandingkan dengan provinsi yang berada di Kawasan Barat Indonesia. Tujuan penelitian ini adalah untuk mengkaji determinan stunting pada anak usia 1-5 tahun di Kawasan Timur Indonesia dengan meneliti faktor maternal. Penelitian menggunakan data sekunder yang diambil dari Indonesian Family Life Survey 5 (IFLS 5). Sampel pada penelitian ini merupakan seluruh anak usia 1-5 tahun yang tinggal di Kawasan Timur Indonesia yang menjadi responden IFLS 5. Variabel terikat adalah kejadian stunting, sedangkan variabel bebas meliputi tinggi badan ibu, tingkat pendidikan ibu, dan usia ibu saat hamil. Data dianalisis menggunakan uji regresi logistik. Hasil penelitian menunjukkan bahwa nilai p untuk tinggi badan ibu = 0,000), tingkat pendidikan = 0,001, dan usia ibu saat hamil = 0,039. Dengan demikian dapat disimpulkan bahwa faktor maternal yang terdiri dari tinggi badan ibu, tingkat pendidikan ibu, dan usia ibu saat hamil merupakan determinan stunting pada balita di Kawasan Timur Indonesia.Kata kunci: stunting; balita; faktor maternal; tinggi badanibu; pendidikan ibu; usia ibu saat hamil